Pengaruh Kualitas Layanan, Kualitas Produk, dan Kepuasan Pelanggan terhadap Word of Mouth pada Jasa Penyedia Layanan Internet Lotus Computama - rian maulana (JURNAL WIRANOMIKA, 2026)
This study aims to examine service quality, product quality, and customer satisfaction at the internet service provider Lotus Computama, as well as to explain how these three aspects contribute to the occurrence of word of mouth among customers. The research employed a qualitative approach using in depth interviews with three informants, the company owner, customer service staff, and an active customer supported by direct observations conducted during installation visits with new customers. The findings indicate that Lotus Computama places strong emphasis on improving service quality by ensuring network stability, accelerating the handling of service disruptions, and providing responsive customer support. High product quality and consistent service further enhance customer satisfaction. The information provided by the three informants was found to be consistent with the results of field observations, thereby strengthening the validity of the data. Overall, the study demonstrates that service quality, product quality, and customer satisfaction have a positive influence on word of mouth, as satisfied customers tend to share recommendations both directly and through various digital communication media.